Desain Over the Air Programming pada Jaringan Sensor Nirkabel Berbasis Platform Arduino - Fajar, Mohammad (STMIK KHARISMA Makassar, 2024)
The purpose of this research is to design over the air programming mechanism for a node in wireless sensor network. Data are gathered from experiments of the proposed system on a constrainted environment. On this design, the Arduino that becomes the target of reprogramming has it’s bootloader modified to enable the capability to run embedded program from the SD Card. Arduino’s source code .ino file is compiled into a .hex file using the Arduino IDE. Then, it is processed using avrdude application into a ready to run firmware binary file on Arduino. A desktop application is made for this mechanism in order to control sender XBee device in transmitting data packet by packet. If the transmission was successful, the node will restart itself, and trigger the bootloader to load new program from the SD Card. The system is evaluated through preset scenarios which including testing at various distances and environments (indoor and outdoor). It was concluded that the reprogramming mechanism was uneffective in transmitting source code when at least one of the XBee devices is located inside the building which affected the transmission process. For the second testing scenario, both nodes were located outdoors with testing distance up to 15 metres, resulting with average transmission speed of 35 bytes per second for sent packet size of 60 bytes. The safest sent packet size to avoid packet loss while transmitting should not exceed 30 bytes for transmission distance up to 15 metres. Transmission speed across all test scenarios ranges between 14 bytes per second to 35 bytes per second. For indoor testing, the evaluation results showed that the designed OTAP mechanism in this study is not yet effective. This is assumed to be influenced by the transmission capability of the XBee communication module.